A Review on the Application of Molecular Dynamics to the Study of Coalbed Methane Geology - Yu, Song; Bo, Jiang; Chongtao, Wei; Xuguang, Dai; Fangkai, Quan; Chenliang, Hou; Guoxi, Cheng (Frontiers in Earth Science, 2021)
Over the last three decades, molecular dynamics (MD) has been extensively utilized in the field of coalbed methane geology. These uses include but are not limited to 1) adsorption of gaseous molecules onto coal, 2) diffusion of gaseous molecules into coal, 3) gas adsorption-induced coal matrix swelling and shrinkage, and 4) coal pyrolysis and combustion. With the development of computation power, we are entering a period where MD can be widely used for the above higher level applications. Here, the application of MD for coalbed methane study was reviewed. Combining GCMC (grand canonical Monte Carlo) and MD simulation can provide microscopic understanding of the adsorption of gaseous molecules onto coal. The experimental observations face significant challenges when encountering the nanoscale diffusion process due to coal structure heterogeneity. Today, all types of diffusion coefficients, such as self-, corrected-, and transport-diffusion coefficients can be calculated based on MD and the Peng-Robinson equation. To date, the MD simulation for both pure and multi-components has reached a situation of unprecedented success. Meanwhile, the swelling deformation of coal has been attracting an increasing amount of attention both via experimental and mimetic angles, which can be successfully clarified using MD and a poromechanical model incorporating the geothermal gradient law. With the development of computational power and physical examination level, simulation sophistication and improvements in MD, GCMC, and other numerical models will provide more opportunities to go beyond the current informed approach, gaining researcher confidence in the engagement in the estimation of coal-swelling deformation behaviors. These reactive MD works have clarified the feasibility and capability of the reactive force field ReaxFF to describe initial reactive events for coal pyrolysis and combustion. In future, advancing MD simulation (primarily characterized by the ReaxFF force field) will allow the exploration of the more complex reaction process. The reaction mechanism of pyrolysis and spontaneous combustion should also be a positive trend, as well as the potential of MD for both visualization and microscopic mechanisms for more clean utilization processes of coal. Thus, it is expected that the availability of MD will continue to increase and be added to the extensive list of advanced analytical approaches to explore the multi-scaled behaviors in coalbed methane geology.